The impact of stellar feedback from velocity-dependent ionized gas maps – a MUSE view of Haro 11. Issue 3 (3rd June 2019) - Menacho, V; Östlin, G; Bik, A; Della Bruna, L; Melinder, J; Adamo, A; Hayes, M; Herenz, E C; Bergvall, N
ABSTRACT: We have used the capability of the Multi-Unit Spectroscopic Explorer (MUSE) instrument to explore the impact of stellar feedback at large scales in Haro 11, a galaxy under extreme starburst condition and one of the first galaxies where Lyman continuum (LyC) has been detected. Using H α, [O iii ] λ5007, and [O i ] λ6300 emission lines from deep MUSE observations, we have constructed a sequence of velocity-dependent maps of the H α emission, the state of the ionized gas, and a tracer of fast shocks. These allowed us to investigate the ionization structure of the galaxy in 50 km s −1 bins over a velocity range of −400 to 350 km s −1 . The ionized gas in Haro 11 is assembled by a rich arrangement of structures, such as superbubbles, filaments, arcs, and galactic ionized channels, whose appearances change drastically with velocity. The central star-forming knots and the star-forming dusty arm are the main engines that power the strong mechanical feedback in this galaxy, although with different impact on the ionization structure. Haro 11 appears to leak LyC radiation in many directions. We found evidence of a kpc-scale fragmented superbubble that may have cleared galactic-scale channels in the ISM. Additionally, the Southwestern hemisphere is highly ionized in all velocities, hinting at a density bound scenario. A compact kpc-scale structure of lowly ionized gas coincides with the diffuse Lyα emission and the presence of fast shocks. Finally, we find evidence that a significant fraction of the ionized gas mass may escape the gravitational potential of the galaxy.